Modification of the hemodynamic and molecular features of phosphine, a potent mitochondrial toxicant in the heart, by cannabidiol. (4th May 2022) - Hooshangi Shayesteh, Mohammad Reza; Haghi-Aminjan, Hamed; Baeeri, Maryam; Rahimifard, Mahban; Hassani, Shokoufeh; Gholami, Mehdi; Momtaz, Saeideh; Salami, Seyed Alireza; Armandeh, Maryam; Bameri, Behnaz; Samadi, Mahedeh; Mousavi, Taraneh; et al.
Abstract: Aluminum phosphide (AlP) poisoning is common in many countries responsible for high mortality. The heart is the main target organ in AlP poisoning. Several studies have reported the beneficial effects of cannabidiol (CBD) in reducing heart injuries. This study aimed to investigate the possible protective effect of CBD on cardiac toxicity caused by AlP poisoning. Study groups included almond oil, normal saline, sole CBD (100 µg/kg), AlP (11.5 mg/kg), and four groups of AlP + CBD (following AlP gavage, CBD administrated at doses of 5, 25, 50, and 100 μg/kg via intravenous ( iv ) injection). Thirty minutes after AlP treatment, an electronic cardiovascular device (PowerLab) was used to record electrocardiographic (ECG) changes, heart rate (HR), and blood pressure (BP) for three hours. Cardiac tissue was examined for the activities of mitochondrial complexes, ADP/ATP ratio, the release of cytochrome C, mitochondrial membrane potential (MMP), apoptosis, oxidative stress parameter, and cardiac biomarkers at 12 and 24 hours time points. AlP administration caused abnormal ECG, decreased HR, and BP. AlP also significantly reduced mitochondrial complex I and IV activity and ADP/ATP ratio. The level of cytochrome C release, apoptosis, oxidative stress, and cardiac biomarkers was considerably increased by AlP, which was compensated following CBD administration. CBD was able to improve hemodynamic function to some extent in AlP poisoned rats. CBD restored ATP levels and mitochondrial function and decreased oxidative damage and thus, prevented the heart cells from entering the apoptotic stage. Further clinical trials are needed to explore any possible benefits of CBD in AlP-poisoned patients.